Asian Options, the Sum of Lognormals, and the Reciprocal Gamma Distribution - Milevsky, Moshe Arye; Posner, Steven E. (Journal of Financial and Quantitative Analysis, 1998)
Moshe Arye Milevsky, Steven E. Posner, Asian Options, the Sum of Lognormals, and the Reciprocal Gamma Distribution, The Journal of Financial and Quantitative Analysis, Vol. 33, No. 3 (Sep., 1998), pp. 409-422